How is India doing on malnutrition and non-communicable diseases? Insights from the National Family Health Surveys (2005-06 to 2019-21) - Kapoor, Rati; Singh, Nishmeet; Nguyen, Phuong Hong; Singh, S. K.; Dwivedi, L. K.; Pedgaonkar, Sarang; Puri, Parul; Chauhan, Alka; Khandelwal, Shweta; Chamois, Sylvie (International Food Policy Research Institute, 2023)
A set of global nutrition targets for maternal and child nutrition together with diet related non communicable diseases ( to be achieved by 2025 was endorsed by the World Health Assembly in 2013 These targets provide goals against which progress towards ending malnutrition in all its forms can be measured and contribute to the Sustainable Development Goals This data note describes trends in multiple forms of malnutrition and NCD outcomes at the national, state, and district levels for India using survey data from NFHS 3 2005 06 NFHS 4 2015 2016 and NFHS 5 2019 2021 Insights on other malnutrition targets such as anemia and breastfeeding will be forthcoming